Analyzing Digital Marketing Strategies to Increase Student Enrollment in Private Universities: An Educational Management Perspective - Martiman S Sarumaha (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze digital marketing strategies in an effort to increase the number of new students in private universities from the perspective of educational management. This study also explores how educational management designs, implements, and evaluates digital marketing strategies in the context of increasingly dynamic competition in the higher education sector. This study uses a literature study method with a descriptive qualitative approach. Based on its analysis, this study concludes that effective digital marketing for private university enrollment hinges not on technical platform sophistication, but on its strategic integration within the institution's educational management framework. It identifies a critical "Strategic Content-Resource Alliance Gap" between ideal content strategies and the often insufficient institutional resources and managerial analysis required to implement them. Consequently, the value of any digital tactic must be measured by its alignment with the university's strategic positioning and the sustainability of its resource commitment. The study further critiques the common disconnect in literature between marketing tactics and core management theories. Thus, it recommends practical steps like digital resource audits, cross-functional teams, and integrated metrics, arguing that digital marketing must be cultivated as a core strategic capability not just a promotional tool to achieve lasting competitive advantage.